The dataset of in-situ measurements of chemically and radiatively important atmospheric gases from the AGAGE and affiliated stations (2022R1) - Ronld Prinn; Ray Weiss; Jgor Arduini; Tim Arnold; Paul Fraser; Anita Ganesan; Jimmy Gasore; Christina Harth; Ove Hermansen; Jooil Kim; Paul Krummel; Zoë Loh; et al. (ESS-DIVE: Deep Insight for Earth Science Data, 2022)
In the ALE/GAGE/AGAGE global network program, continuous high frequency gas chromatographic measurements of four biogenic/anthropogenic gases (methane, CH4; nitrous oxide, N2O; hydrogen, H2; and carbon monoxide, CO) and several anthropogenic gases that contribute to stratospheric ozone destruction and/or to the greenhouse effect have been carried out at five globally distributed sites for several years. The program, which began in 1978, is divided into three parts associated with three changes in instrumentation: the Atmospheric Lifetime Experiment (ALE), which used Hewlett Packard HP5840 gas chromatographs; the Global Atmospheric Gases Experiment (GAGE), which used HP5880 gas chromatographs; and the present Advanced GAGE (AGAGE). AGAGE uses two types of instruments: a gas chromatograph with multiple detectors (GC-MD), and a gas chromatograph with mass spectrometric analysis (GC-MS). Beginning in January 2004, an improved cryogenic preconcentration system (Medusa) replaced the absorption-desorption module in the GC-MS systems at Mace Head and Cape Grim; this provided improved capability to measure a broader range of volatile perfluorocarbons with high global warming potentials. The Medusa GC-MS systems were subsequently used at other AGAGE stations (Trinidad Head, Barbados, American Samoa, Zeppelin, Jungfraujoch, and Goan) after the initial setup at Mace Head and Cape Grim. More information may be found at the AGAGE home page: https://agage.mit.edu/instruments. Data from the AGAGE and affiliated stations (total of 9 sites) between August 1993 and March 2021 are provided in “Agage_gcmd_gcms_data_2022_05_26_tar.gz” (compressed tar file). The metadata file has information on each station and currently released species. The standard scales used in archived species are listed in "AGAGE_scale_2022_v1.pdf". Additional information can be found on the AGAGE website (https://agage.mit.edu).